EVALUATION OF TUBERCULOSIS RECORDING AND REPORTING CASE SYSTEM AT SYARIF HIDAYATULLAH HOSPITAL IN 2020 - Ratnasari, Yunita; Sjaaf, Amal Chalik (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2023)
The national TB control program target is TB elimination at 2035 and TB eradication at 2050. Hospitals must establish a DOTS Team who have responsibility to implementing the TB control program and must be record and report any disease cases. TB case reporting uses the Integrated Tuberculosis Information System (SITT) since 2020. Integrated Tuberculosis Information System has become the Tuberculosis Information System (SITB). Syarif Hidayatullah Hospital is one of the 3 hospitals that have not completed the report. This research is a descriptive analytic study with a qualitative approach. The data collecting data include documents review, observation, and in-depth interviews with key informants. The results showed that recording and reporting did not run optimally because 1) the lack of human resources such as nurses as the spearhead of manual record, 2) there was no funding for the TB DOTS program including for recording and reporting, 3) Hospital Information System was not integrated into all service units causing difficulties in data collection TB patients, 4) the internal network did not working properly because there is no socialize about TB recording and reporting flowchart. Increased management commitment in implementing the TB DOTS program so that recording and reporting can working properly.